Diseño de una máquina trituradora a rodillos y controlador de diámetro, para la obtención de áridos de tamaño máximo 8mm; para la empresa HORMYPOL. - Briceño Sarmiento, María Verónica (2010)
In summary, within the investigative process of this project, carried out the design of a shredding machine and driver roller diameter, to obtain 8 mm maximum size aggregates, thus providing an optimal solution for the company Hormypol. The crusher consist as a cornerstone of two rolls of 120mm diameter by 600mm long with a wheelbase of 128mm, which will be ready four rows of ten teeth on each roll with a separation of 90 ° between rows, the motion transmission be done through gears, the operating speed of the rollers is 30rpm, with a 15HP engine. The aggregate crushing roller is designed for crushing capacity of 874.8 cubic meters per hour.